2009
DOI: 10.1007/s10825-009-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Basis-set choice for DFT/NEGF simulations of carbon nanotubes

Abstract: We investigate the effect of the choice of the basis set on the results of ab initio (density functional theory/nonequilibrium Green's function) calculations of the bandgap of semiconducting carbon nanotubes, and near-zero-bias conductance of metallic carbon nanotubes. Both ideal and deformed carbon nanotubes are studied, as well as nanotubes with an adsorbed biomolecule. The results show that the near-zero-bias conductance of armchair nanotubes can be calculated accurately with a minimal basis set, with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 13 publications
(29 reference statements)
1
16
0
1
Order By: Relevance
“…The basis set used in the ab initio simulations can significantly affect the results, even qualitatively, as we have previously demonstrated [23,24]. Therefore, we first made a test with the (9,0) tube, where we repeated the bare-tube simulations and the simulations with arginine using the double-zeta (DZ), double-zeta polarized (DZP), and single-zeta-polarized (SZP) basis sets.…”
Section: Simulated Structuresmentioning
confidence: 99%
“…The basis set used in the ab initio simulations can significantly affect the results, even qualitatively, as we have previously demonstrated [23,24]. Therefore, we first made a test with the (9,0) tube, where we repeated the bare-tube simulations and the simulations with arginine using the double-zeta (DZ), double-zeta polarized (DZP), and single-zeta-polarized (SZP) basis sets.…”
Section: Simulated Structuresmentioning
confidence: 99%
“…The basis sets used the single-zeta polarized (SZP), and the double-zeta polarized (DZP). 20,21 The DZP is the mostly complete basis set we used, and therefore the one that best predicts the ground state of the system. 21 To understand the localization of electrons near the Fermi level, we have plotted the density of states profile of the three proposed models using the ATK-DFT.…”
Section: Resultsmentioning
confidence: 99%
“…A lot of theoretical and experimental studies showed that the electronic properties of nanotubes are mainly determined by the chirality and diameter of nanotube. The band structure calculation results show that single-walled carbon nanotubes have a conductor and semiconductor properties, which has been confirmed by experiment [7][8][9][10]. Part of single-walled silicon nanotubes were studied by using first-principles method and molecular dynamics method [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 82%